Determinants of Taxpayer Compliance in MSMEs registered at KPP Pratama Karawang Utara - Luciani, Veni; Yanti, Yanti; Rachpriliani, Awaliawati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The study aims to evaluate and test the impact of tax understanding, mental accounting and the level of trust tax confidence on compliance with MSMEs tax obligations registered in the KPP Pratama Karawang Utara. This research uses quantitative methods using primary data. The population in this study is the entire MSMEs tax liability registered in KPP Pratama Karawang Utara. Sample on this research as many as 100 MSMEs tax obligations registered in KPP Pratama Karawang Utara. The sampling technique uses purposive sampling with criteria based on gender, age, having a NPWP, type of business, length of business and turnover. This research model uses PLS. The findings of this study show that tax understanding has a positive influence on MSMEs tax compliance. Calculation of tax liability MSMEs tax likewise with a level of trust that influences on compliance with MSMEs tax obligations with a significant value of 0.05. The results of the research show that the rate of tax payments will be imposed on the cars with the turnover criteria ranging between 250-50 million, 100-300 million and above 300 million.